Perfusion of isolated rat kidney with Mesenchymal Stromal Cells/Extracellular Vesicles prevents ischaemic injury. Issue 12 (21st June 2017) - Gregorini, Marilena; Corradetti, Valeria; Pattonieri, Eleonora Francesca; Rocca, Chiara; Milanesi, Samantha; Peloso, Andrea; Canevari, Silvana; De Cecco, Loris; Dugo, Matteo; Avanzini, Maria Antonietta; Mantelli, Melissa; Maestri, Marcello; et al.
Abstract: Kidney donation after circulatory death (DCD) is a less than ideal option to meet organ shortages. Hypothermic machine perfusion (HMP) with Belzer solution (BS) improves the viability of DCD kidneys, although the graft clinical course remains critical. Mesenchymal stromal cells (MSC) promote tissue repair by releasing extracellular vesicles (EV). We evaluated whether delivering MSC‐/MSC‐derived EV during HMP protects rat DCD kidneys from ischaemic injury and investigated the underlying pathogenic mechanisms. Warm ischaemic isolated kidneys were cold‐perfused (4 hrs) with BS, BS supplemented with MSC or EV. Renal damage was evaluated by histology and renal gene expression by microarray analysis, RT‐PCR. Malondialdehyde, lactate, LDH, glucose and pyruvate were measured in the effluent fluid. MSC‐/EV‐treated kidneys showed significantly less global ischaemic damage. In the MSC/EV groups, there was up‐regulation of three genes encoding enzymes known to improve cell energy metabolism and three genes encoding proteins involved in ion membrane transport. In the effluent fluid, lactate, LDH, MDA and glucose were significantly lower and pyruvate higher in MSC/EV kidneys as compared with BS, suggesting the larger use of energy substrates by MSC/EV kidneys. The addition of MSC/EV to BS during HMP protects the kidney from ischaemic injury by preserving the enzymatic machinery essential for cell viability and protects the kidney from reperfusion damage.